PANDANGAN AL QURAN TENTANG PEMBANGUNAN EKONOMI BERBASIS KESETARAAN GENDER - Yaqin, Ainol (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2015)
Al Quran is the first and primary reference for any problems Muslims faced. This holy book becomes guidelines and directions of Muslim’s life throughout the ages. In line with the changes and development of times, there are various problems in law, social, cultural and others emerging in the middle of life. Among them is the issue of gender which is also reflected in the Quran. Quran contains universal values as the guide for human life at all times. The values are always relevant to be implemented in every place, day and time, among others are humanities, justice, freedom, and equality values. Related to the values of justice and equality, Quran never tolerates differences and subordinated treatment or even discrimination among human beings. Quran explains the sameness and equality between men and women. Therefore, they have the same duties and responsibilities as abdullah and caliph in the earth. Human capacity as caliph serves to preserve, manage and prosper the earth. Achieving prosperity is done in various aspects of life, in the fields of economics, culture, science and so on.